Features of Administrative-Procedural Status of the Parties - Khachikyan, Tigran (Bulletin of Yerevan University C: Jurisprudence, 2022)
The article discusses the nature of the rights and obligations of the parties and the legal validity of their implication. With this regard, the article refers to the existing authorizations and the issues arising during their application in practice, which is presented in the context of the implementation of the principle of ex officio. As the subject of separate analysis, the institute of representation is studied, discussing its features in administrative proceedings. The main issue is that the current legislation allows the court to remove the representative from the proceedings in any case if he is not capable to represent the party. Within this framework, it was stated that although the aforementioned judicial discretion cannot be extended to an attorney or a legal or official representative, the norm is formulated in a manner that does not provide an opportunity to identify the criteria on the basis of which the court can exercise its discretionary power.